Abroad but not abandoned: supporting student adjustment in the international placement journey. Issue 6 (3rd June 2021) - Conroy, Kieran M.; McCarthy, Lucy
ABSTRACT: International work placements are an increasingly important way for universities to enhance their internationalisation strategies and develop student learning. However, the increase in student mobility internationally has not been paralleled in the level of support received from the university when undertaking international placements. Using an action research qualitative design, we explore how students may be supported in effectively managing international placements. Data were collected from UK Business School students through focus groups, interviews and reflections. Findings identify a variety of important support structures that can be implemented to aid students in adjusting to three main challenges; professional, cultural and personal. We argue that these supports need to be developed across three interrelated stages in the international placement process; pre-departure, post-arrival and repatriation.